PETROMINERALOGICAL AND GEOCHEMICAL STUDIES OF HAVELIAN BARITE, HAZARA, NWFP, PAKISTAN - KHAN, HAMEEDULLAH; HUSAIN, VIQAR; QURESHI, KHALID; PASHA, KAMAL (Biological Sciences - PJSIR, 2022)
The epigenetic vein type barite deposits occur at several localities near Havelian in limestone and shale sequence belonging to Eocene age. Barite veins varying in thickness from a few inches to several feet occur in grey coloured argillaceous limestone and shale. Thin bands of barite and galena are also seen in some samples. Important minerals occuring along with barite are calcite, quartz and magnesite. In polished sections, galena, pyrite and goethite were also identified. Petrographically, barite occurs in several textural types: massive, crystalline, lath or platy shaped ranging from fine to coarse in size. The BaS04 content in Havelian barite samples ranges from 20 to 92%. Major impurities are Si02, CaO, MgO, Fe203 and A1203. Barite deposits in Havelian are structurally controlled vein and cavity filling type deposits. These barite deposits have not been developed and mined systematically. Baritedeposits of this district are good in quality and need detailed investigations for determining mineable reserves. The physical and chemical characteristics of Havelian barite show their suitability for paint, paper, rubber, petroleum drilling and chemical industries with or without processing.